Antonio J. Guirao, Vicente Montesinos and Václav Zizler, Open problems in the geometry and analysis of Banach spaces. Cham: Springer 2016, xii + 169 p., ISBN 978-3-319-33571-1/hbk; 978-3-319-33572-8/ebook. - COBZAȘ, S. (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
This is a collection of 304 open research problems from Banach space theory and related areas (measure theory, vector measures, nonlinear analysis, best approximation and optimization).